Dukungan Instrumental Keluarga Berkaitan Dengan Konsumsi Sayur Dan Kunjungan Posyandu Lansia Hipertensi Pada Masa Pandemi Covid-19 - Armiyati Raddi Kaka; Ronasari Mahaji Putri; Ragil Catur Adi Wibowo (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2022)
The elderly experience aging and declining health, so they need to consume vegetables and participate in posyandu activities as health services for the elderly. Family support gives meaning to the elderly. The aim of the study was to find out the link between family instrumental support and vegetable consumption, visiting hypertensive elderly during the Covid-19 pandemic at the Anggrek Mulyoagung Posyandu Malang. Cross sectional research design. A sample of 54 respondents from a population of 62 elderly, using accidental sampling. The instrument is a questionnaire, with Fisher's Exact and Chi Square data analysis tests. The results of the study were that most of the 33 (61.1%) respondents received less family instrumental support; Half of the 27 (50.0%) respondents consumed vegetables in the less category and most of the 35 (64.8%) respondents did not routinely attend posyandu visits. There is a relationship between family instrumental support and consumption (p value 0.002) and family instrumental support with hypertensive elderly visits during the Covid-19 pandemic (p value = (0.000)). The next researcher examined the perceptions of elderly people based on the HBM (Health Belief Model) with visits posyandu elderly in posyandu